2014
DOI: 10.1371/journal.pone.0099093
|View full text |Cite|
|
Sign up to set email alerts
|

Unexpected Patterns of Admixture in German Populations of Aedes japonicus japonicus (Diptera: Culicidae) Underscore the Importance of Human Intervention

Abstract: The mosquito Aedes japonicus japonicus, originally restricted to temperate East Asia, is now widespread in North America and more recently has become established in Europe. To ascertain the putative number of separate introductions to Europe and examine patterns of expansion we analyzed the genetic makeup of Ae. j. japonicus populations from five cemeteries in North Rhine-Westphalia and Rhineland-Palatinate, two western German federal states, as well as of specimens from populations in Belgium, Switzerland, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 44 publications
1
70
0
Order By: Relevance
“…For example, in an extensive review of medfly (Ceratitis capitata) studies, Malacrida et al (2007) found that multiple introductions consistently contribute to the maintenance or enhancement of genetic diversity in this important global invader. Similar processes have been described in invasive populations of the Eucalyptus Bronze Bug, Thaumastocoris peregrinus (Nadel et al 2009), Harlequin Ladybird, Harmonia axyridis (Lombaert et al 2010), Red Tomato Spider Mite, Tetranychus evansi (Boubou et al 2012), Eastern Subterranean Termite, Reticulitermes flavipes (Scaduto et al 2012), mosquito Aedes japonicas japonicas (Zielke et al 2014), and a number of other insect invaders (Table S1). The changing nature of invasive alien populations caused by multiple introductions over time highlights the need to periodically reassess diversity in such populations (something that is not currently being done routinely for most invasive populations), especially in light of the implications this can have for management, as discussed below.…”
Section: Patterns Of Global Insect Movementsupporting
confidence: 63%
“…For example, in an extensive review of medfly (Ceratitis capitata) studies, Malacrida et al (2007) found that multiple introductions consistently contribute to the maintenance or enhancement of genetic diversity in this important global invader. Similar processes have been described in invasive populations of the Eucalyptus Bronze Bug, Thaumastocoris peregrinus (Nadel et al 2009), Harlequin Ladybird, Harmonia axyridis (Lombaert et al 2010), Red Tomato Spider Mite, Tetranychus evansi (Boubou et al 2012), Eastern Subterranean Termite, Reticulitermes flavipes (Scaduto et al 2012), mosquito Aedes japonicas japonicas (Zielke et al 2014), and a number of other insect invaders (Table S1). The changing nature of invasive alien populations caused by multiple introductions over time highlights the need to periodically reassess diversity in such populations (something that is not currently being done routinely for most invasive populations), especially in light of the implications this can have for management, as discussed below.…”
Section: Patterns Of Global Insect Movementsupporting
confidence: 63%
“…Currently , Ae. japonicus is known from six European countries [30], including Belgium [26], The Netherlands [30], and is regarded as established in Switzerland [26], Austria and Slovenia [29]. Since 2008, Ae.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus and from Schaffner et al [26]; Huber et al [27]; Huber et al [19]; Krebs et al [28]; Zielke et al [29]; Melaun et al [18] and Zielke et al [30] for Ae. japonicus .…”
Section: Methodsmentioning
confidence: 99%
“…Both these types of DNA loci are highly variable and provide useful and somewhat independent information on demographic history [46]. We found evidence of multiple separate introductions to the USA and to Europe that often mixed and expanded [41,42,47 …”
Section: Methodsmentioning
confidence: 76%
“…Currently, Ae. j. japonicus has multiple expansion foci in Germany, Switzerland and on both sides of the border between Austria and Slovenia [41].…”
Section: Methodsmentioning
confidence: 99%